Hospital Brand Management Practices and Promotions in Tamil Nadu - Parameshwaran, R.; Sharma, Mahesh Chandra (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
In this paper, the authors discuss the hospital brand management practices and promotion strategies in Tamil Nadu that look at the effect of strategic branding on the perception of patients, trust, and institutional performance. When viewed in a competitive healthcare setup, Indian hospitals use brand management to differentiate their services, improve customer loyalty, and develop long-term credibility, especially in states of the developed healthcare market, such as Tamil Nadu. Previous studies prove that the branding of hospitals can help to increase outpatient trust and referrals to a significant level when paired with effective communication and quality indicators displayed in hospitals. The research incorporates both quantitative and qualitative approaches based on surveying patients and conducting interviews with administrators, respectively, which will give deep insights into the operational practices, as well as the perception of stakeholders. The results indicate that patients know about a product and make a choice in response to well-organized brand vision, stable service quality, and the use of digital presence, as the determinants of a high brand equity. Social media advertising and digital marketing present themselves in a rather promising way as one of the most useful tools of attracting the attention of younger and digitally-oriented patients to complement the traditional outreach and community programmes. This study adds to the knowledge on healthcare marketing as it contextualizes the brand management concept to the various hospital industries in Tamil Nadu and recommends strategic directions to improve the effectiveness of brands by managers and policymakers. When promotional activities are supported by ethical standards, patient-centric values, and technology, hospitals will be able to bolster reputation capital and enhance long-term growth in healthcare service provision.